Renovation Measures for Reduction of Primary Energy Consumption and CO2 Emissions of Hospital Building - Džana Kadrić; Rejhana Blažević; Hadis Bajrić; Adna Peco; Edin Kadrić (Tehnički Glasnik)
Hospitals, as highly energy-intensive buildings, significantly contribute to a country's energy consumption and CO2 emissions. The study focuses on a hospital building in Sarajevo, Bosnia and Herzegovina, and investigates the impact of selected energy renovation measures on hospital primary energy consumption and CO2 emissions. The main goal of this paper is to develop a mathematical model for establishing relationship between primary energy consumption and CO2 emissions (responses), and the three renovation measures (factors). The research uses dynamic simulation of the building's energy performance in Design Builder, validated with the actual energy consumption. Three energy renovation measures were considered in the study: installation of thermal insulation on external walls and flat roof, and the installation of a photovoltaic power plant. The Analysis of Variance and regression analysis were used to estimate factor effects, and to develop mathematical models. The analysis revealed that the installation of photovoltaic power plant on the roof and thermal insulation on the external walls had the most significant impact on reducing the building's primary energy consumption and CO2 emissions. Installation of insulation on the roof did not significantly affect these performances compared to the other two measures. Developed models are suitable for evaluation of potential for energy and CO2 savings through the implementation of energy efficiency measures. Study results can be extrapolated to all buildings within the same category, providing a valuable tool for energy efficiency planning in the healthcare sector.